Hacia una crítica a la sociología de la transición: reflexiones sobre la paradoja de la desinstitucionalización en el análisis de las trayectorias de jóvenes vulnerables en Argentina - Roberti, Eugenia (El Colegio de México, 2017)
The article reconstructs the trajectories of young people in a peripheral neighborhood of Buenos Aires, analyzing practices and subjective valuations about school, work and family. In a context of deep transformations in the condition of youth, this research analyzes the breakdown of the linear model of the transition to adulthood. It also describes the paradoxes in the process of deinstitutionalization of the life course, offering a glimpse into the increasing relevance of new relational supports in shaping youth trajectories.